Respiration of barley seeds (Hordeum vulgare L.) under different storage conditions - Taher, Hernán Ignacio; San Martino, Silvina; Abadia, María Bernadette; Bartosik, Ricardo Enrique (Elsevier, 2023)
The changes in oxygen (O2) and carbon dioxide (CO2) concentrations were characterized during the hermetic storage of barley seeds (Hordeum vulgare L.) in glass jars at different temperatures (5, 15, 25, and 35 °C) and moisture content levels (12%, 14%, and 16%). Gas concentration curves were analyzed using both linear and non-linear models to describe the trends. The respiration rate was determined for each temperature and moisture content combination as storage time advanced and O2 was consumed. The performance of the models was assessed using an independent dataset. The values of respiration rates obtained in this study were from −0.1103 to −56.0336 mg O2/(kgDM d) and from 0.0136 to 71.8876 mg CO2/(kgDM d), and accumulated dry matter loss was computed based on these respiration rates. Our study confirms that the respiration of barley seeds is greatly influenced by the aw conditions. Respiration rates of the seeds are negligible when the aw falls below 0.7. However, as the aw surpasses this threshold, respiration rates gradually increase due to microbial activity. Temperature also exerts a significant influence on the respiration rate of barley seeds. Furthermore, as the aw conditions increase, the respiratory quotient also increases, approaching a value of 1 as the aw approaches 0.7. These findings provide valuable information for understanding the dynamic of respiration and optimizing storage conditions to maintain barley seed quality during long-term storage.